Realization of the key image «creation» in D. Samoylov poetic speech - Гамали, Ольга Игоревна; Каневская, Ольга Борисовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article considers the peculiarities of realizing the key image «creation» in D. Samoylov's poetic speech. It is established that the image under analysis represents the author's poetic credo through intermediary of such words as creativity (творчество), poet (поэт), poetry (поэзия), word (слово), verse (стих), painting (живопись), music (музыка), artist (художник). The components of the image «creation» are «art», «creator / poet», «author». The verbalizators of these images undergo diversified semantic transformation. D. Samoylov employs the variety of tropes: metaphors, epithets, similes, personifications, rhetorical questions. The numerous anthroponyms (the names of famous artists) link the works of the author to the world culture.